Diesel biodiesel blends influence in the behavior of the effective and environmental parameters of an internal combustion engine diesel of 6,11 kw - Mejía R., Antonio (2017)
This research was conducted at Combustion Engines Institute of the Mechanic Engineering Faculty in National Engineering University of Lima. The aim of this research is to evaluate the influence of Diesel blends biodiesel B10, B20 and B30 in the effective and environmental operating parameters of internal combustion Diesel engine 6.11 kW. The results obtained with the Diesel biodiesel blends and the B5 commercial fuel, after the measurements made in the engine, let us obtain and graph the characteristics of speed and load of the engine used in this research, showing a variation in the effective and opacity parameters so, the hypothesis given can be contrasted and the conclusions can be presented.